New Hopes in Retinoblastoma Treatment - ÇEKİÇ, OSMAN; AKKAYA TURHAN, SEMRA (AKAD DOKTORLAR YAYINEVI, 2014)
Survival rates of retinoblastoma have increased dramatically during the last decade. The current major treatment modalities for retinoblastoma include enucleation, intravenous chemoreduction, external beam therapy, focal treatments (such as brachytherapy and transpupillary thermotherapy), subconjunctival chemotherapy and selective ophthalmic artery chemotherapy. Although current treatment modalities have improved survival rates as well as eye salvage, new treatment modalities are expected to arise in the near future, since above mentioned non-targeted treatments have extensive side effects. Recent advances in genetic analysis of retinoblastoma 1 (RB1) mutations and pathways leading to retinoblastoma may provide vital information for the development of new targeted therapies which are less toxic.
Keywords: Genetics; Retinoblastoma; RB1 mutation; Targeted treatments; GENOMIC INSTABILITY; TARGETING HYPOXIA; P53 PATHWAY; TUMOR; PROTEIN; PROGRESSION; INHIBITORS; RETINOMA; THERAPY; P21